(untitled) (Archive of Conferences, 2021)
The reliability of the process of mechanical spinning of cotton on the receiving and transmitting device was studied, experimental research was carried out on selected cotton varieties C-6524 I and III. The actual weight of the first grade cotton in the cart with the cart trailer was 1.4-1.6 tons, the actual weight of the third grade cotton was 1.9-2.1 tons. By making adjustments to the theoretical calculations, it was learned that the actual capacity of the bunker for dumping 2 tons of cotton should be 7.8 m3, for dumping 1.5 tons of cotton - 6.4 m3. Taking into account these factors, it is necessary to increase the capacity of the receiving hopper to 14 m3, to separate the front side of the conveyor, and to use a special moving bar to prevent the process of spilling on the surface of the conveyor.